1998
DOI: 10.3109/03639049809085635
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dissolution Rate of Indomethacin by Adsorbents

Abstract: Samples of indomethacin and kaolin or microcrystalline cellulose (Avicel) were prepared by solvent deposition or simple blending methods. Dissolution rates of these samples were studied. The surface adsorption of indomethacin on the studied adsorbents was shown to improve the dissolution rate of the drug in water. The solvent-deposited samples of indomethacin on kaolin or Avicel in the ratio 1:4 released 25% of the drug at 34 or 60 min, respectively (t25%), while 25% of the pure drug was released at 140 min. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Many workers have designed a miniscular drug form using excipients with high surface area. 29,30 The reduction in peak intensity of XRPD spectra of agglomerates of batches IT-1 and IT-2 supported the observation (Figure 3). Decrease in peak intensities was due to dilution and formation of some plate-type crystals.…”
Section: Resultssupporting
confidence: 73%
“…Many workers have designed a miniscular drug form using excipients with high surface area. 29,30 The reduction in peak intensity of XRPD spectra of agglomerates of batches IT-1 and IT-2 supported the observation (Figure 3). Decrease in peak intensities was due to dilution and formation of some plate-type crystals.…”
Section: Resultssupporting
confidence: 73%
“…MCC is known to cause deaggregation of powders, increasing the effective surface area in contact with the medium (Scheme 2; Cases 2 and 3). 8 Therefore, the dissolution rate enhancement is attributed to particle deaggregation in the dissolution medium. Microscopic examination revealed that the theophylline monohydrate particles formed during the dissolution run (Case 3 in Scheme 2) were much larger than the theophylline monohydrate in the granules (Case 2 in Scheme 2).…”
Section: Effect Of Processing With Microcrystalline Cellulosementioning
confidence: 99%
“…In addition to the active ingredient, the excipients in a dosage form can influence product performance. 8 Thus, product performance will be influenced by the solid state of the drug and excipients, as well as the processing conditions. These effects are of particular concern in case of drugs with low…”
mentioning
confidence: 99%
“…Very few researchers have prepared miniscular dosage forms by using excipients with a large surface area [27,28]. Pawar et al designed a miniscular dosage form for ibuprofen-talc byCCA.…”
Section: Fig 5: X-ray Powder Diffraction Pattern Of Pure Linezolid Amentioning
confidence: 99%